Pelatihan Peningkatan Kemampuan Public Speaking Melalui Storytelling - Maria Angelina Molo; Vensensius Januar Sole; Innosensia E. Isavela Nd Satu (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The ability to speak up front is often a problem in building relationships or socializing between people. Low public speaking skills in students will have a big impact on information seeking activities both sources and content of information. So that the accuracy and quality of information becomes less besides that it also has something to do with student confidence. pengabdi sees that there is a need for training activities which will certainly help students in improving their public speaking skills. However, pengabdi also saw other problems that existed. So that the pengabdi chose to use the storytelling technique in providing services to students of SMP Negeri 4 Pasir Putih. The purpose of this service activity is to provide training on how to conduct public speaking activities by utilizing storytelling media. The location of the service is SMPN 4 Pasir Putih, Nagawutung District, Lembata Regency, East Nusa Tenggara on July 27, 2024. the author concludes that public speaking activities are basic abilities that must be possessed by every human being. However, to be able to convey information well, one's public speaking skills must be formed since education.